Supersensitive photon upconversion based immunoassay for detection of cardiac troponin I in human plasma - Raiko Kirsti; Lyytikäinen Annika; Ekman Miikka; Nokelainen Aleksi; Lahtinen Satu; Soukka Tero (ELSEVIER, 2022)
Background and aims: Upconverting nanoparticles (UCNPs) are attractive reporters for immunoassays due to their excellent detectability. Assays sensitive enough to measure baseline level of cardiac troponin I cTnI in healthy population could be used to identify patients at risk for cardiovascular disease. Aiming for a cTnI assay of such sensitivity, the surface chemistry of the nanoparticles as well as the assay reagents and the protocol were optimized for monodispersity of the UCNP antibody conjugates (Mab UCNPs) and to minimize their non-specific interactions with the solid support.
Materials and methods: UCNPs were coated with poly(acrylic acid) via two-step ligand exchange and conjugated with monoclonal antibodies. The conjugates were applied in a microplate-based sandwich immunoassay using a combination of two capture antibodies to detect cTnI. Assay was evaluated according to guidelines of Clinical & Laboratory Standards Institute.
Results: The limit of detection and limit of blank of the assay were 0.13 ng/L and 0.01 ng/L cTnI, respectively. The recoveries were >90% in spiked plasma in the linear range. The within- and between-run imprecisions were <10%.
Conclusion: The results demonstrate that UCNPs enable quantification of cTnI concentrations expected in plasma of healthy individuals and could be used to identify patients at risk for cardiovascular disease.